THE DEVELOPMENT OF THE INDONESIAN CRIMINAL CODE DERIVED FROM THE YUDICIAL PARDON VALUE IN ISLAMIC LAW - Wahyuningsih, Sri Endah; Hafidz, Jawade (LPPM IAIN Kudus, 2017)
This paper aims to make efforts to develop the Criminal Code derived from the yudicial pardon value in Islamic law as a law that lives and thrives in society. The Criminal Code as the basis of criminal law enforcement is a legacy of the Dutch era which do not know peace to end up the case. It is not in accordance to Pancasila as the basis for legal development in Indonesia. Research method used socio legal and qualitative data analysis. The result of the research claims that Islamic law is a legal source in the development of the justice Criminal Code, forgiveness is possible in the jarimah-hudud and qisas-diyat in solving the criminal case. Implementation in the development of the Criminal Code needs to be added to the reason for the abolition of criminal prosecution if between the perpetrator and the victim is already forgiven, further, in the case of a crime with a slight loss the judge may decide to be forgiven even if the defendant is found guilty.